HAEMATOLOGY AND SERUM BIOCHEMISTRY OF PIG FED GROWER FEED FORTIFIED WITH COCOA (Theobroma cacao) SEED TESTA. - Akinduro, Victor Olabisi (Journal of Agricultural Sciences (Belgrade), 2022)
The on-farm attempt to cut down feed cost through bulk fortification of standard animal feed with available cheap conventional feed ingredients or wastes had been a normal practice without known empirical impact on livestock health and wellbeing. Therefore, this study determined the haematological parameters and serum biochemistry of pigs fed cocoa (Theobroma cacao) seed testa at varying inclusion levels in the formulated standard grower pig feed; 0% cocoa seed testa (T1), 25% cocoa seed testa (T2), 50% cocoa seed testa (T3), 75% cocoa seed testa (T4) and 100% cocoa seed testa (T5). Thirty (30), 8 weeks old pigs were randomly assigned to the five treatments of six pigs each and replicated thrice, with two pigs per replicate in a completely randomized design (CRD) experiment. The experiment lasted for 10 weeks. At the end of the feeding trial, blood samples were collected randomly from three pigs per treatment through the jugular vein using hypodermic needle and syringe for haematological analysis and serum biochemistry. This study recorded significant differences (P<0.05) in most of the haematological parameters, except for white blood cell (WBC), platelet and heterophils; apart from high density lipoprotein, all serum biochemical indices were also significantly different (P<0.05). Haematological parameters and serum indices were within the normal range for healthy pig except lymphocytes. However, the study revealed that haematological indices and the serum biochemical parameters indicated that cocoa seed testa at 25% level in the standard grower pig feed had the optimum support for the wellbeing and healthy performance of pigs.